2012
DOI: 10.1136/bmjopen-2012-001148
|View full text |Cite|
|
Sign up to set email alerts
|

Exposure to selective serotonin reuptake inhibitors and the risk of congenital malformations: a nationwide cohort study

Abstract: ObjectivesTo analyse the relation between selective serotonin reuptake inhibitor (SSRI) use and major congenital malformations, with focus on malformations of the heart.DesignRegister-based retrospective nationwide cohort study, using the Danish Medical Birth Registry.SettingDenmark.ParticipantsPregnant women in Denmark between 1997 and 2009 and their offspring.Primary outcome measuresFor each SSRI, ORs for major congenital malformations were estimated using multivariable logistic regression models for women e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
150
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(164 citation statements)
references
References 44 publications
(42 reference statements)
13
150
1
Order By: Relevance
“…A study by Malm and colleagues has found that women taking SSRIs show a 10 fold greater incidence of Fetal Alcohol Spectrum Disorders (FASD) compared with women not on SSRIs [43]. These findings are supported by adverse event reports of FASD and behavioral effects consistent with FASD to FDA for all SSRIs and reports of SSRIs causing compulsive alcohol intake [84].…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…A study by Malm and colleagues has found that women taking SSRIs show a 10 fold greater incidence of Fetal Alcohol Spectrum Disorders (FASD) compared with women not on SSRIs [43]. These findings are supported by adverse event reports of FASD and behavioral effects consistent with FASD to FDA for all SSRIs and reports of SSRIs causing compulsive alcohol intake [84].…”
Section: Resultssupporting
confidence: 66%
“…Nothing better illustrates this than the evidence from Malm et al study [43], which is consistent with known effects of SSRIs in triggering alcohol intake in a sub-population of subjects and a recent RCT showing poorer drinking outcomes with citalopram treatment for alcohol dependence disorder [118].…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Contrary to positive associations, there are many reviews pretending no relationship between antidepressant use and congenital malformations (3). In a study by JimenezSolem et al, authors submitted that women using antidepressant treatment tend to visit health care providers for screening their children and this tendency might be accepted as a confounding factor (4). In addition to vast literature about results of antidepressant use in pregnancy suggesting no significant increase in malformations in the offspring, no concrete evidence about their teratogenicity has been emerged (5).…”
Section: Possible Risks For the Offspringmentioning
confidence: 99%
“…49, 60, 64, 70, 86, 90, 103, 104, 114-116, 120, 125, 147, 150 Two of the studies were methodologically strong, with low risk of bias, 104,125 and two were methodologically weak, high risk of bias, due primarily to potentially biased selection of patients, lack of assessment of comparability of subjects at baseline, and lack of appropriate statistical analysis, including controlling for potential confounding. 103,115 Because major malformations are a fairly rare and serious adverse event, a signal from indirect evidence may be important.…”
Section: Congenital Anomaliesmentioning
confidence: 99%